Construction and efficacy of group psychological training program for recruit training squad leaders based on psychological capital theory - LUO Qingqing; LUO Qingqing; DU Jun; JIA Zhen (陆军军医大学学报, 2023)
Objective To establish a group psychological training program for improving the psychological capital of recruit training squad leaders, and to explore its intervention efficacy for their psychological capital and work engagement. Methods Delphi method was used to construct a psychological training program to improve the psychological capital of recruit training squad leaders. With convenient sampling, 71 recruit training squad leaders were enrolled from April 1 to May 30, 2023, and then randomly divided into experimental group (n=35, 6 times of psychological training, for 2 hours each time, twice a week) and control group (n=36, routine training). Pre-test, post-test and one-month follow-up measurements were conducted using Psychological capital questionnaire(PCQ) and Utrecht work engagement scale(UWES) in both groups. Results ① The expert authority coefficient (Cr) of the 2 rounds of expert consultation was 0.905, the positive coefficient was 100%, and the Kendall coordination coefficient was 0.142 and 0.260 (P < 0.001). The psychological capital group training program had 6 first-level indicators and 24 second-level indicators. ② After the intervention, the group-by-time interaction between the experimental group and the control group showed that the total scores of psychological capital and work engagement were significantly higher in the experimental group than the control group (Wald Chi-square=60.341, 101.410; P < 0.001). Conclusion Group training program can significantly improve the psychological capital and enhance work engagement for recruit training squad leadser.